Effect of low-intensity pure tone auditory stimulation on patients with rapid eye movement sleep behavior disorder. (1st September 2016) - Zhang, Lin; Xu, Yixin; Zhuang, Jianhua; Peng, Hua; Wu, Huijuan; Zhao, Zhengqing; He, Bin; Zhao, Zhongxin
Abstract : Objective: This study aimed to investigate the influence of low-intensity pure tone auditory stimulation on patients with rapid eye movement (REM), sleep behavior disorder (RBD), and attempt to identify a new method of RBD intervention. Methods: Patients diagnosed with idiopathic RBD (iRBD) or symptomatic RBD (sRBD) were given auditory stimulation of low-intensity pure tones during their REM sleep. Sleep parameters including sleep process, sleep architecture as well as eye movements (EMs) frequency, and amplitude were recorded by polysomnography monitoring at pre-, intra-, and post-stimulation. Results: Thirteen iRBD and 18 sRBD patients completed this study. Auditory stimulation significantly reduced the EMs frequency and amplitude in iRBD and sRBD patients ( p  < 0.05). In the iRBD group, the intra-stimulated FSL increased significantly than the pre-stimulated FSL ( p  < 0.05). After stimulation, patients had similar sleep latency (FSL), rapid eye movement sleep latency (RSL) and periodic limb movements in sleep (PLMS) compared with control. In the sRBD group, the intra-stimulated total sleep time, sleep efficiency was significantly increased, whereas the RSL and PLMS were significantly reduced compared with the pre-stimulated ones (all p  < 0.05). The sRBD patients had similar time in bed, FSL and RBD episodes compared with control (all p  < 0.05) in spite of significant difference before stimulation (all p  < 0.05). However, the sleep architecture was not influenced by the stimulation despite the decrease in N3% in iRBD group ( p  < 0.05). Conclusion: Low-intensity pure tone auditory stimulation may be a potentially effective intervention for RBD, especially for sRBD.